Предмет: Математика,
автор: ulove3695varya
9*x-(x+6) при x=-8
Помогите пожалуйста
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
9x-(x+6) = 9х - х - 6 = 8х - 6
При х = -8
8х - 6 = 8*(-8) -6 = -64 - 6 = - 70
Автор ответа:
0
Ответ:
-70
Пошаговое объяснение:
9×х-(х+6), при х= -8
9×(-8)- (-8+6)= -70
1) 9×(-8)=-72
2) -8+6= -2
-72- (-2)= - 70
Похожие вопросы
Предмет: Другие предметы,
автор: kukieva
Предмет: Русский язык,
автор: YANASWEET
Предмет: Английский язык,
автор: melodyamalibu
Предмет: Геометрия,
автор: Chappie8106
Предмет: Биология,
автор: crazzyboy123